The Impact of Transformational Leadership and Project Success: Mediating Role of Team Identity, Team Communication, and Team Empowerment - Siddiqui, Aqeel Wahab; Shaukat, Muhammad Bilal (2024)
This study is grounded in the theoretical frameworks of the Resource Base View and Social-Identity Theories and intents to evaluate how the adoption of transformational leadership practices influences project success by considering facilitating function of team-identity, team-communication, and team empowerment. The study was conducted among 350 Software project professionals in Pakistan. The study utilized PLS-SEM to analyze both direct and mediating effects. The findings revealed a notable affiliation between TL and PS. Besides, the study confirmed that team identity, communication, and empowerment act as mediator in the connection amid TL and PS. This research addresses a gap in empirical studies within developing countries, notably Pakistan by shedding light on how TL impacts PS through the lens of team-dynamics. This study stands as an early exploration into the interplay among proposed association.